An exploratory nomogram model with 18F-FDG PET/CT metabolic parameters for predicting high-risk status of microvascular invasion in hepatocellular carcinoma patients prior to liver transplantation - Li, Shichang; Guo, Ai’nan; Wang, Xue; Tian, Ying; Zhang, Fang; Wei, Lingge; Fu, Peng (Journal of Gastrointestinal Oncology; Vol 17, No 2 (April 30, 2026): Journal of Gastrointestinal Oncology, 2026)
There are still difficulties in dividing patients into an microvascular invasion (MVI) high-risk and non-high-risk group among hepatocellular carcinoma (HCC) patients based on the pathology findings. This study investigated preoperative fluorine-18-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET)/computed tomography (CT) (18F-FDG PET/CT) quantitative metabolic parameters and developed an exploratory nomogram model with these parameters for predicting high-risk MVI in patients with HCC scheduled for liver transplantation.